2022
DOI: 10.1186/s12870-022-03656-z
|View full text |Cite
|
Sign up to set email alerts
|

The involvement of extracellular ATP in regulating the stunted growth of Arabidopsis plants by repeated wounding

Abstract: Background Extracellular ATP (exATP) has been shown to act as a signal molecule for regulating growth, development, and responses of plants to the external environment. Results In this study, we investigated the possible involvement of exATP in regulating the stunted growth caused by repeated wounding. The present work showed that the repeated wounding caused the decreases in leaf area, fresh weight, dry weight, and root length of Arabidopsis seedl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 66 publications
3
3
0
Order By: Relevance
“…To evaluate the impact of the truncated P2K1 on morphometric phenotypes in response to ATP treatment, we transferred 5 days seedlings to media supplemented with 500 μ m ATP. Consistent with prior reports [36], growth on 500 μ m ATP for 24 h resulted in a modest but statistically significant reduction in root growth in the wild‐type (Fig. 3A,B).…”
Section: Resultssupporting
confidence: 92%
“…To evaluate the impact of the truncated P2K1 on morphometric phenotypes in response to ATP treatment, we transferred 5 days seedlings to media supplemented with 500 μ m ATP. Consistent with prior reports [36], growth on 500 μ m ATP for 24 h resulted in a modest but statistically significant reduction in root growth in the wild‐type (Fig. 3A,B).…”
Section: Resultssupporting
confidence: 92%
“…Indeed, it has been long demonstrated that an increasing number of wounds trigger a more robust defence response in tomato plants (Green and Ryan, 1972), which may, in turn, generate a more impactful and easily detectable trade-off to development. This hypothesis may also be expanded to other plant species, as the frequently documented wound-induced growth repression in A. thaliana is observed under protocols that cause substantial damage to the leaves, in a similar manner to those applied in our experiment (Yan et al, 2007;Zhang and Turner, 2008;Fiorucci et al, 2022;Shi et al, 2022). Interestingly, the observation that gentle types of environmental inputs such as rain, wind, touch, and even sound waves can arrest plant development (Braam and Davies, 1990;Waterman et al, 2019;Matsumara et al, 2022) may indicate that plants utilize different signalling cascades to perceive and differentially respond to specific types of mechanical stimuli.…”
Section: Discussionsupporting
confidence: 64%
“…At this age, MT plants usually have two to four true leaves, all of which were wounded in a consecutive manner (see methods) for a total of ten wounds per plant. Measurements of shoot growth rate indicate that, as observed for A. thaliana (Yan et al, 2007;Zhang and Turner, 2008;Fiorucci et al, 2022;Shi et al, 2022), repetitive mechanical wounding significantly reduces the size of tomato plants (Figures 1B-C). Despite statistical significance in growth reduction (p<0.05, according to Student's t-test) was only observed seven days after wounding (7 DAW, 32 d of age), shoot growth rate changed at early time points (3 and 4 DAW, 28 and 29 d of age, respectively) when compared to unwounded control (Figure 1B).…”
Section: Mechanical Wounding Hinders Tomato Developmentsupporting
confidence: 56%
“…The signalling pathway from eATP to wounding/immunity transcription runs through the plasma membrane legume-like lectin serine-threonine receptor kinase “ DO es not R espond to N ucleotides1” (DORN1/P2K1) and also its co-receptor phosphorylation target P2K2, although whether all cell types deploy this co-receptor is unknown ( Choi et al., 2014 ; Jewell et al., 2019 ; Pham et al., 2020 ). Wound-induced inhibition of plant growth is mediated by P2K1 ( Shi et al., 2022 ) and this receptor is required for limiting infection by bacteria, oomycetes and fungi ( Gouget et al., 2006 ; Bouwmeester et al., 2011 ; Bouwmeester et al., 2014 ; Balagué et al., 2017 ; Chen et al., 2017 ; Tripathi et al., 2018 ; Nizam et al., 2019 ; Kumar et al., 2020 ). Overexpression of P2K1 can confer resistance to insect and nematode attack ( Jewell et al., 2022 ).…”
Section: Eatp Signalling Intersects With Multiple Pathwaysmentioning
confidence: 99%